Institutional Support as a Determinant of Career Development of Female Librarians in Federal Universities in Southwestern Nigeria - Ogundipe, T. C.; Adisa, Aminat Omolola (International Journal of Natural and Practical Sciences (IJNPS), 2025)
This study examines institutional support and career patterns as determinants of the career development of female librarians in federal universities in Southwestern Nigeria. The descriptive survey was adopted for the study. The population comprises all female librarians in seven universities in Southwestern Nigeria. The total enumeration method was used to sample all female librarians, and a self-designed questionnaire was the instrument for data collection. Data were analysed using descriptive statistics, Pearson Product-Moment Correlation and multiple regression analysis. The results showed career development of female librarians, who engage in networking activities, pursue professional development, seek mentorship or guidance and satisfaction with the level of recognition among others. Institutional support for the career development of female librarians in federal universities in Southwestern Nigeria is significant. Female librarians in Southwestern Nigeria engage in more networking, pursue professional development and seek mentorship. University library management in Southwestern Nigeria should provide opportunities for leadership roles, clear and transparent promotion criteria for their career development and set out clear policies for promotion.